The cultural revolution and science policy and development in mainland China. - Lie Tektjeng, Some Indonesian remarks on modern China studies: the great proletarian cultural revolution as seen from Jakarta (Centre d'Etude du Sud-Est asiatique et de l'Extrême- Orient, 1971)
Courrier de l'Extrême-Orient. Stencil.